(untitled) (Coordinates of Public Administration, 2026)
The article analyses the phenomenon of covert (passive) aggression within the professional environment of the civil service as a specific form of conflict behaviour characterised by a discrepancy between outwardly correct, formally loyal interaction and an internal experience of hostility, dissatisfaction, and an intention to exert indirect psychological influence on others. It is demonstrated that under heightened requirements for ethical conduct, impartiality, observance of hierarchical subordination, and standards of public behaviour, passive aggression may function as a «latent mechanism» for expressing frustration, disagreement, and resistance to managerial decisions without overt confrontation. The study elucidates the psychological antecedents and mechanisms of passive-aggressive manifestations, including avoidance of direct conflict, fear of adverse sanctions, diminished capacity for open position-assertion, and the desire to minimise personal responsibility for escalating tension. In this context, typical instruments of indirect influence are examined: ironic framing and sarcastic remarks, deliberate delays in task completion, selective «forgetting» of agreements, covert sabotage, demonstrative indifference, and communicative neglect. It is shown that the systematic reproduction of such practices erodes trust, distorts horizontal coordination, generates chronic tension, and, consequently, diminishes the organisational performance of public authorities. Particular attention is devoted to the relationship between covert aggression, organisational unpreparedness for social diversity, and practices of latent discrimination. It is specified that bias towards «otherness» (in particular, towards persons with non-normative sexual identity and gender affiliation) may manifest through microaggressions — «jokes», insinuations, exclusion from informal communication, devaluation of professional contributions, and selective application of informal rules. Such actions often lack the features of a direct breach of internal regulations; however, in practice, they reproduce inequality, reinforce stigmatisation, and increase the conflict potential of the workplace. The article substantiates that the legal and ethical requirements of the civil service (principles of non-discrimination, respect for human dignity, integrity, and accountability) require instrumental reinforcement through applied managerial measures: systematic staff training in emotional self-regulation, conflict-management competence, cultural sensitivity, and constructive communication, as well as the introduction of early-response procedures and mediation practices in cases of protracted intra-organisational tensions.